Proses Penjaringan dan Penyaringan Calon Anggota Legislatif Perempuan di Kota Padang - Saili, Syamsir; Suryanef, Suryanef (Jurnal Demokrasi, 2005)
This study tried to describe the recruitment process of women candidate of Legislative Body members in Padang City handled by some popular political parties. Qualitaive approach was used in this study. The finding of this study indicated that every political parties had different policies in their recruitment process of Legislative Body members, including for women candidates.In addition, the implementation 30% quota of women representation in the recruitment process still had some problems, like the lack of qualified women candidates, inconsistency of the political party leaders to implement the regulation, etc. Kata Kunci: rekrutmen, keadilan gender, penjaringan dan penyaringan, keterwakilan perempuan